159k views
1 vote
Subtract 5p + 8q from the sum of 5p + 4q and – 9p + 69.


User Jbub
by
5.2k points

2 Answers

1 vote
Answer: -9p - 4q + 69

Step-by-step explanation:

(5p + 4q + (-9)p + 69) - (5p + 8q)
= 5p + 4q - 9p + 69 - 5p - 8q
= -9p - 4q + 69
User Lynden Shields
by
5.7k points
4 votes

Answer:

-9p -4q + 69

Step-by-step explanation:

5p +4q + (-9p +69)

=> 5p + 4q -9p +69

=> -4p +4q +69

Now, we need to subtract 5p +8q from -4p + 4q +69

=> -4p +4q +69 - (5p +8q)

=> -4p + 4q +69 - 5p -8q

=> -9p -4q + 69

User Demonedge
by
5.9k points